INCREASED KNOWLEDGE ABOUT PLAQUE AND TARTAR IN ELEMENTARY SCHOOL STUDENTS IN KESAMBI VILLAGE, TEGAL REGENCY - Ratnawati, Irma Dewi; Pratiwi, Rosa; Mayangsari, Regilia Shinta; Nurazky, Savira; Indrawati, Silvia Vera; Dimas P. P., Muhammad (Jurnal Pengabdian Masyarakat DentMas, 2023)
Background: Dental and oral hygiene is a special concern for school-age children. Children who are not used to keeping their teeth and mouth clean will tend to experience dental problems. This problem begins when an imbalance of mineralization and demineralization in children causes microorganisms to enter the mouth. These microorganisms will stick to and develop on the teeth which begins with the appearance of plaque and tartar in children. Riskesdas 2018 data shows that 93% of children in Indonesia experience cavities. The data shows that the level of awareness to maintain dental and oral hygiene is still low, so educational efforts are needed to increase children's knowledge. This study provides media interventions in the form of posters, 3D media, and video playback to children to attract children's attention to understand and improve dental and oral hygiene behavior. Method: This research method uses an experimental method that is directly given to elementary school students in Kesambi Village, Tegal Regency. The number of students who participated in this was 55 people with an age range of 9 - 12 years. This research started by giving a questionnaire, then giving the material, and filling out the questionnaire. The results of the questionnaire will be processed and entered into the SPSS data. Result: Knowledge before and after the extension intervention has increased as evidenced by a significant increase. This is in accordance with the results of the p-value which shows 0.000, which means that there is a significant difference before and after penuluhan. Conclusion: Based on the results of the study, it can be concluded that counseling about children's plaque and tartar conducted on elementary school students in Kesambi Village is effective because it gets significant results.